Selecting sweet spots for the exploitation of tight oil reservoirs from logs: case studies. Issue 4 (4th July 2019) - Liu, Zhidi; Shi, Yujiang; Zhou, Jinyu; Wang, Changsheng; Zhang, Peng; Ma, Tinghao
Abstract : The optimal selection of sweet spots for the exploitation of tight oil reservoirs is very important when formulating a development programme. Sweet spots for the exploitation of tight oil reservoirs are closely related to reservoir quality, hydrocarbon source rock quality and completion quality. In this study, criteria for the classification of sweet spots are established using a tight reservoir of fine sandstone in the first member of the Qingshankou Formation in Daqingzijing Oilfield, China as the study site. The results indicate that the vast majority of the research area includes type I and type II sweet spots. Type I sweet spots are located in the west and northwest of the research area and in the central region around wells H71 and H116; type II are located in the northeast and south of the research area, as well as in the region around the type I sweet spots. In the well region of type I sweet spots, the oil/gas is relatively enriched, and the fracability of the reservoir stratum is strong; these are key areas for tight oil development in the research area. Comparison of the evaluation results with well testing data indicates that the effect of well fracturing is obvious for type I sweet spots and the corresponding oil yield is high. The results of well fracturing are also adequate for type II sweet spots and the oil output can reach industry standards, although the corresponding yield is relatively low. Wells in non-sweet spots are unlikely to be fractured successfully, and even if they are, the oil output cannot reach industry standards.